Correlation between Apolipoprotein B/Apolipoprotein A-I Ratio with Atherogenic Index of Plasma among Acute Myocardial Infarction Patients - Winardi Emmanuel Setiawan; Anggoro Budi Hartopo; Royhan Rozqie (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Acute myocardial infarction (AMI) is the most common cause of death in the world. One preventive attempt to reduce AMI is early detection of blood lipid profile. A simple method of lipid profile assessment is the measurement of atherogenic index of plasma (AIP), meanwhile more accurate method of lipid profile assessment is the measurement of apolipoprotein B/apolipoprotien A-I (ApoB/ApoAI) ratio. However, whether both measurements are interchangeable is need to be investigated. This study aims to investigate the correlation between AIP value and ApoB/ApoAI ratio in patients with AMI.METHODS: The study design was cross-sectional study. The blood samples of consecutively enrolled AMI patients had been selected after inclusion and exclusion criteria. The blood samples were taken within 24 hours of patient admission to the hospital. The blood concentration of high-density lipoprotein (HDL) and triglycerides (TG) were measured using turbidimetric method. The AIP was calculated as logarithmic of TG/HDL ratio (log10.[TG:HDL]) The concentration of ApoB and ApoAI were measured using immunoturbidimetric method. The correlation between these measurements was analyzed with Pearson correlation test.RESULTS: The blood samples of 76 subjects were collected and analyzed. The subjects were dominated by male (n=67, 88%) and those whose age ≥55 years old (n=54, 71%). The mean ApoB value was 88.66 mg/dL and ApoAI was 97.39 mg/dL. The AIP value was 0.05. The Pearson correlation test between AIP and ApoB/ApoAI ratio showed a significant positive correlation with the strength of correlation was moderate (r=0.51, p-value<0.01).CONCLUSION: There was a significantly positive and moderate correlation between AIP value and ApoB/ApoAI ratio in acute myocardial infarction patients.KEYWORDS: atherogenic index of plasma, acute myocardial infarction, apolipoprotein B/apolipoprotein A-I ratio